Does Recognition versus Disclosure Affect Value Relevance? Evidence from Pension Accounting - Yu, Kun (The Accounting Review, 2013)
ABSTRACT This study examines whether institutional ownership and analyst following affect the value relevance of disclosed versus recognized pension liabilities. Using a sample of firms with pension liabilities that were disclosed under SFAS No. 87 and subsequently recognized under SFAS No. 158 from 1999 to 2007, I find that off-balance-sheet pension liabilities are more value relevant for firms with a higher level of institutional ownership or analyst following in the pre-158 period. More importantly, I find that SFAS No. 158 increases the value relevance of previously disclosed off-balance-sheet pension liabilities for firms with a low level of institutional ownership or analyst following, and that the increase in the value relevance becomes less pronounced for firms with a higher level of institutional ownership or analyst following. Overall, the results are consistent with the view that institutional ownership and analyst following affect the value relevance of disclosed information as well as the valuation difference between disclosed and recognized information. This study also highlights the importance of considering institutional ownership and analyst following in the value-relevance research. Data Availability: All data are publicly available from the sources indicated in the text.